2017
DOI: 10.1055/s-0036-1588406
|View full text |Cite
|
Sign up to set email alerts
|

Carbon–Carbon and Carbon–Heteroatom Bond-Forming Transformations Catalyzed by Calcium(II) Triflimide

Abstract: The aim of this short review is to highlight the interest of using Ca(NTf 2) 2 as catalyst in CC and C-X bond-forming reactions. The ability of this complex to activate alcohols, alkenes, ketones, and cyclopropanes towards nucleophilic additions and other chemical processes is shown though a set of selected examples, which illustrate the substrate scope and the synthetic applications offered by this 'green' calcium salt. 1 Introduction 2 Synthetic Applications 3 Conclusion Key words ammonium salt, calcium, CC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 32 publications
0
24
0
Order By: Relevance
“…As part of our continuing efforts to expand the reactivity of unactivated alkenes, this reaction piqued our attention. In previous studies, we have demonstrated that the association of a catalytic amount of calcium­(II) salts with hexafluoroisopropanol (HFIP) , was a powerful synthetic tool regarding the hydroamidation of unactivated alkenes and the hydroarylation of highly deactivated styrenes . In these reactions, the role of calcium is not to act as a traditional Lewis acid that will activate either the nucleophile or the olefin but, instead, to strengthen the acidity of H-bond clusters of HFIP and trigger the hydrofunctionalization process .…”
mentioning
confidence: 99%
“…As part of our continuing efforts to expand the reactivity of unactivated alkenes, this reaction piqued our attention. In previous studies, we have demonstrated that the association of a catalytic amount of calcium­(II) salts with hexafluoroisopropanol (HFIP) , was a powerful synthetic tool regarding the hydroamidation of unactivated alkenes and the hydroarylation of highly deactivated styrenes . In these reactions, the role of calcium is not to act as a traditional Lewis acid that will activate either the nucleophile or the olefin but, instead, to strengthen the acidity of H-bond clusters of HFIP and trigger the hydrofunctionalization process .…”
mentioning
confidence: 99%
“…Future tasks related to the chemistry of these s-block organometallics include stability and reactivity [17], catalysis and stoichiometric conversions [18,21], Lewis acidity and nucleophilicity [24]. Quantum chemical calculations are valuable tools to elucidate the agostic and π-interactions between the s-block metal ions and multiple bonds [25,26].…”
Section: Toxicity Of Elementmentioning
confidence: 99%
“…In contrast to the wide applications of limestone being used as the building materials, the use of this element as catalyst has been underexploited for quite a long time. Investigations on Ca catalysis are just unfolding in the past decade and a series of interesting reactions have been reported [11][12][13][14][15][16]. Recently, during our ongoing investigations on green catalysis [17][18][19][20][21][22], it was unexpectedly found that the Ca(OH) 2 possessed superior catalytic activities over the conventionally used NaOH or KOH catalysts and these interesting results shifted our attention to the subject of Ca catalysis [20][21][22].…”
Section: Introductionmentioning
confidence: 99%